The location of Kant's refutation of idealism - Watt, R (Wiley, 2017)
Many philosophers have been puzzled by Kant's decision to insert the Refutation of Idealism into the second edition of the first Critique at the end of his elucidation of the Second Postulate. This article proposes a solution to the puzzle. It defends an explanation for the location of Kant's Refutation of Idealism that is plausibly expressed by Kant's claim at the end of his elucidation of the Second Postulate that the Refutation of Idealism is ‘here in its right place’ because ‘[a] powerful objection against these rules for proving existence indirectly is made by idealism’ (B274). According to this explanation, the Refutation of Idealism is Kant's response to the objection that the Second Postulate must be false since otherwise idealism is true. This article also considers and rejects a number of alternative explanations for the location of Kant's Refutation of Idealism.